Role of Cyclic Nucleotide Gated Channels in Stress Management in Plants - K. Jha, Saroj; Sharma, Manisha; K. Pandey, Girdhar (Current Genomics, 2016)
Tolerance of plants to a number of biotic and abiotic stresses such as pathogen and herbivore attack, drought, salinity, cold and nutritional limitations is ensued by complex multimodule signaling pathways. The outcome of this complex signaling pathways results in adaptive responses by restoring the cellular homeostasis and thus promoting survival. Functions of many plant cation transporter and channel protein families such as glutamate receptor homologs (GLRs), cyclic nucleotidegated ion channel (CNGC) have been implicated in providing biotic and abiotic stress tolerance. Ion homeostasis regulated by several transporters and channels is one of the crucial parameters for the optimal growth, development and survival of all living organisms. The CNGC family members are known to be involved in the uptake of cations such as Na+, K+ and Ca2+ and regulate plant growth and development. Detail functional genomics approaches have given an emerging picture of CNGCs wherein these protein are believed to play crucial role in pathways related to cellular ion homeostasis, development and as a ‘guard’ in defense against biotic and abiotic challenges. Here, we discuss the current knowledge of role of CNGCs in mediating stress management and how they aid plants in survival under adverse conditions.
Keywords: Calcium signaling